Analisis Faktor-Faktor Yang Mempengaruhi Penundaan Proses Klaim Jaminan Hari Tua (JHT) BPJS Ketenagakerjaan Cabang Belu Dengan Menggunakan Regresi Linear Berganda - Yohana Noviayanti Da Silva Toti; Eva Binsasi; Grandianus Seda Mada (Fakultas Pertanian, Universitas Timor, 2023)
In serving BPJS Ketenagakerjaan participants who make claims for Old Age Benefits (JHT), delays in the claim process often occur. This is due to the fact that the file for submitting a claim is not complete, the officer is overwhelmed because the accumulation of files is increasing and they have to divide their time to do other tasks outside the office. This study aims to see which variables between data completeness and working hours fullness have a more significant effect on delays in claims for Old Age Security (JHT) at the Belu Branch of the Employment Social Security Administration Agency (BPJSTK) and find out the multiple linear regression model. Based on the results of data processing, it can be concluded that the data completeness variable has a more significant effect than the fullness of working hours on delays in JHT claims. The regression model obtained is Y^ = 144.458 – 118.141 + 66.814 .